2015
DOI: 10.1002/adv.21559
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Electrospinning of Calcium-Containing Polyurethane Urea

Abstract: Calcium‐containing segmented polyurethane urea was synthesized using a calcium salt of p‐aminobenzoic acid, polytetramethylene glycol, and 4,4′‐methylene bis(cyclohexyl isocyanate) and thereafter fabricated into three‐dimensional scaffolds for the use in biomedical applications. Biocompatibility evaluation of the polymer showed that this newly developed metal‐containing polyurethane urea demonstrated good cytocompatibility and hemocompatibility. The fabricating ability of the metal‐containing polymer was studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“… 75 However, some reports claimed that the nanofibers’ tensile strength increased with the fiber diameter increase. 76 78 This behavior was observed for a polyurethane-based electrospun fiber scaffold, which has a chemical nature similar to our PCUUs. Han et al concluded that the lower tensile strength in the case of small-diameter fibers was caused by weaker junctions of interconnected fibers.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“… 75 However, some reports claimed that the nanofibers’ tensile strength increased with the fiber diameter increase. 76 78 This behavior was observed for a polyurethane-based electrospun fiber scaffold, which has a chemical nature similar to our PCUUs. Han et al concluded that the lower tensile strength in the case of small-diameter fibers was caused by weaker junctions of interconnected fibers.…”
Section: Resultssupporting
confidence: 72%
“…Theoretically, the orientation within fibers on the molecular level increases with decreasing fiber diameter, resulting in a higher mechanical strength. , Therefore, it is expected that with decreasing fiber diameter, the tensile strength of the electrospun fiber increases . However, some reports claimed that the nanofibers’ tensile strength increased with the fiber diameter increase. This behavior was observed for a polyurethane-based electrospun fiber scaffold, which has a chemical nature similar to our PCUUs. Han et al concluded that the lower tensile strength in the case of small-diameter fibers was caused by weaker junctions of interconnected fibers .…”
Section: Resultsmentioning
confidence: 59%
“…Another factor that can influence the mechanical properties is the applied electrical voltage [38c,68a,70] . An increase in the electrospinning voltage can alter the shape of the initial droplet, consequently changing the fiber shape from a typical cylindrical to a beaded or string‐of‐pearl structure.…”
Section: Factors Affecting Mechanical Propertiesmentioning
confidence: 99%
“…However, some reports claimed that the tensile strength of the nanofibers increased with increase of the fiber diameter. [ 67,68 ] Both Nair and Parameswaran and Han et al found the trend of increase in the tensile strength with increasing fiber diameter for a polyurethane‐based electrospun fiber scaffold [68a,b] . They inferred that the lower tensile strength for small‐diameter fibers was due to the weaker junctions of interconnected fibers.…”
Section: Factors Affecting Mechanical Propertiesmentioning
confidence: 99%